TOTAL BAKTERI ASAM LAKTAT, TOTAL ASAM, NILAI pH, SINERESIS, TOTAL PADATAN TERLARUT DAN SIFAT ORGANOLEPTIK YOGHURT METODE BACK SLOOPING - Rizki Adrianto; Damar Wiraputra; Masmulki Daniro Jyoti; Arifia Zulaika Andaningrum (Jurnal Agritechno, 2020)
This study aims to determine the total lactic acid bacteria, total acid, pH value, syneresis, and organoleptic properties of yogurt using the back slooping method. Experiments were made by taking bacteria from yogurt products (biocul) with variations in the incubation time of room temperature, 37 oC, 40 oC, 45 oC, and 37 oC to 40 oC. The results of the analysis on total lactic acid bacteria, total acid, pH value, and viscosity of yoghurt with the back slooping method gave different results. Meanwhile, the organoleptic test used the hedonic level of preference, which included aroma, color, texture, and overall acceptance. Total lactic acid bacteria 8,03-8,29 log CFU / ml; total acid 0.95-1.26%; pH value 3.70-4.78; total dissolved solids 10.1-12.0%; Organoleptic test with the level of preference including color, aroma, texture and overall acceptance, obtained a preference score of 4, which means like. Based on the organoleptic test, it can be concluded that the best quality of yogurt with the back-loop method of incubation temperature of yogurt B5 with an incubation temperature of 37 oC to 40 oC